The Possibility of Using Monte Carlo Method in the Case of Decision-Making under Conditions of Risk Concerning an Agricultural Economics Issue - Dominika Crnjac Milić; Dino Masle (Ekonomski Vjesnik, 2013)
Monte Carlo method is a probabilistic computer algorithm in which the value of one or more random variables is given by the density function, and the goal of which is to predict all the possible outcomes of a process it has been applied to and the probability of their occurrence. As such, the Monte Carlo method proves to be extremely useful in the process of decision- making under conditions of risk. This paper discusses an example of function optimization with the aim of finding a solution that will deliver the highest profits in the described agricultural economics-related problem under risk-free conditions. A Monte Carlo simulation is carried out and the solution under conditions of risk is also found. For that purpose, a special program code was written.